Bureaucratic and Collaborative Governance in Urban Waste Management: Evidence From Padang City - Tirza Haqia Purnama; Roni Ekha Putera; Nika Saputra; Edi Hasymi; Aqil Teguh Fathani; Tengku Rika Valentina; Nabilaa Binti Mohamed (Universitas Muhammadiyah Sidoarjo, 2026)
This study analyzes the implementation of bureaucratic reform in the Padang City Environment Agency (DLH) in the context of institutional strengthening and collaborative governance in waste management. The waste issue in Padang City has become increasingly crucial which reaches more than 600 tons per day. Bureaucratic reform is being pursued to strengthen institutions, improve governance, and encourage cross-sector collaboration among government, the private sector, and the community. However, studies examining how regional bureaucratic reform is substantively linked to collaborative environmental governance at the local agency level remain limited. This study employed a qualitative approach with a descriptive phenomenological method and involved 12 informants, consisting of 4 structural officials, 3 functional officials, 2 community leaders, and 3 collaborative partners representing CSR-related institutions and environmental communities. Primary data were obtained through in-depth interviews, while secondary data were collected from policy documents and scientific publications. The results show that bureaucratic reform at DLH remains largely administrative, as reflected in changes in job nomenclature and the use of E-Kinerja to document weekly activities, attendance lists, photographs, and digital reports, which improved accountability but did not fully transform bureaucratic work culture. Cross-sector collaboration has shown positive progress, particularly through CSR support for waste containers and transport facilities and through community participation in waste-related programs, although it remains constrained by limited resources, technical regulations, and inter-actor coordination. This study confirms that institutional reform requires the internalization of performance values and stronger citizen participation to generate substantive impacts on sustainable waste management.